Urine catecholamine concentrations and psychophysical stress in elite tennis under practice and tournament conditions - Ferrauti, A.; Neumann, G.; Weber, K.; Keul, J. (The Journal of Sports Medicine and Physical Fitness, 2001)
The purpose of the study was to specify and define the differences of psychophysical stress in elite tennis players under practice and tournament conditions. METHODS: Basal, pre- and postcompetition urine samples of 26 nationally ranked players (NR) were analysed for concentrations of epinephrine (EPI) and norepinephrine (NE) under practice (P) and tournament conditions (T). Results were completed by the values obtained from two internationally ranked players (IR) competing in 6 (player A) and 5 (player B) Davis-Cup matches, respectively. RESULTS: In NR, pre- and postcompetition concentrations for EPI were significantly higher under tournament conditions (T: 1.33+/-0.65 and 3.66+/-2.51 &mgr;g/100 mg creatinine vs P: 0.61+/-0.39 and 0.97+/-0.59 &mgr;g/100 mg creatinine). The NE/EPI ratio showed significantly inverse results (T: 3.53+/-1.87 and 3.58+/-1.59 vs P: 8.08+/-6.99 and 10.03+/-6.58), whereas the concentration of NE did not differ between the two conditions. Significant correlations were found between the level of perceived nervousness (ten-point-likert scale) and the postcompetition concentration of EPI (r=0.491, p<0.05) and the NE/EPI ratio (r=-0.595, p<0.01). Players who felt affected by nervousness in their performance outcome showed significantly lower NE/EPI ratios (2.73+/-1.44 vs 4.49+/-2.54, p<0.05). The Davis-Cup-Players showed intra-individually constant but inter-individually different concentrations of EPI (A= 2.2+/-0.5 vs B= 7.0+/-0.8 &mgr;g/100 mg creatinine), NE (A= 7.4+/-2.2 vs B= 15.5+/-3.2 &mgr;g/100 mg creatinine) and the ratio of NE/EPI (A= 3.7+/-2.2 vs B= 2.2+/-0.7). CONCLUSIONS: In tennis tournaments, sympathetic activity is increased due to a higher psychological stress which may impair performance. Practical efforts should focus on psycho-regulative methods and psychophysical regeneration for players dealing with a chronic sympathetic hyper-activation.